"Cultural dope" and "psychological dope": The ethnomethodological attitude and cultural psychology. (December 2015) - Stam, Henderikus J; Ellis, Basia D
Using articles published in this journal by Brown, McHoul and Rapley in 2001 and Middleton and Lightfoot, also in 2001, we use ethnomethodology as a pretext for discussing the foundation of cultural psychology on the admittedly difficult notion of everyday life and people's methods in negotiating that life. The social ordering of what Garfinkel termed an "immortal ordinary society" is just the kind of ordering the study of which might lead to a cultural psychology that takes seriously the complexities of the everyday. We argue not for a particular kind of method but instead for an ethnomethodological attitude as a potential contributor to the shaping of cultural psychology.